David's Little Lad - Meade, L. T., 1854-1914; Petherick, Horace, 1839-1919 (Salt Lake City, UT : Project Gutenberg, 2013)
"David's Little Lad" by L.T. Meade is a novel written in the late 19th century. The story centers on Gwladys Morgan, a Welsh girl who feels stifled and trapped in her quiet, rural life at Tynycymmer. As the narrative unfolds, her longing for adventure and excitement takes a turn when complicated family dynamics begin to surface, revolving around her brother David, and her beloved but flawed brother Owen, who is returning home after a scandalous past. The opening portion introduces us to Gwladys as she reflects on her life and the men in her family. She feels burdened by a sense of monotony as well as a desire for a larger existence outside the confines of her home. The narrative shifts between her self-pity, the yearning for her brother Owen's return, and the revelation of his troubled past. As Gwladys dreams of adventure, she learns about the responsibility and flaws tied to her family's legacy, particularly concerning Owen's moral failings, setting the stage for her emotional growth and the trials ahead. This initial glimpse into her world highlights themes of familial love, aspirations, and the burdens of reputation, making it an inviting read for those intrigued by character-driven tales. (This is an automatically generated summary.)
Release date is 2013-07-07
Produced by Nick Hodson of London, England
Keywords: Children's stories; Brothers -- Juvenile fiction; Avarice -- Juvenile fiction; Mine accidents -- Juvenile fiction; Wales -- Juvenile fiction